Impact of the COVID-19 pandemic on perceived cardiorespiratory fitness in athlete patients - Gustus, S.; Moulson, N.; Churchill, T. W.; Guseh, J. S.; Petek, B. J.; VanAtta, C.; Baggish, A. L.; Wasfy, M. M. (PM&R, 2022)
Introduction: Cardiorespiratory fitness (CRF), as one of the most potent prognostic factors in medicine, is followed longitudinally to guide clinical management. Coronavirus disease 2019 (COVID-19) pandemic-related changes in lifestyle stand to influence CRF. Objective: To assess the influence of the pandemic on perceived CRF in athlete patients and evaluate how perceived CRF change was related to demographics, pre-pandemic measured CRF, and current physical activity (PA). Design: Prospective cohort study, utilizing electronic survey. Setting: Tertiary care sports cardiology clinical practice. Participants: Adult athlete patients without COVID-19 with pre-pandemic measured CRF using cardiopulmonary exercise testing. Interventions: Not applicable. Main Outcome Measures: Perceived change in CRF since pandemic onset; association between perceived CRF change and demographics, PA, health status, and pre-pandemic measured CRF assessed via analysis of variance (ANOVA). Results: Among 62 participants (male: 71%, 50.1 ± 12.1 years old), 40% (25/62) reported no change and 32% (20/62) reported an increase in perceived CRF since pandemic onset. Among the 27% (17/62) who reported a decrease in perceived CRF, in most (12/17), this was characterized as only mild. Demographics and pre-pandemic measured CRF did not differ across groups of perceived CRF change. Participants with a moderate or greater decrease in perceived CRF regarded their overall health (via Euro Quality of Life Visual Analogue Scale) as worse than other groups (ANOVA, p = .001). Although total PA was similar across groups, those who had improvement in perceived CRF reported higher levels of moderate intensity PA (ANOVA, p = .008). Conclusions: The majority of participants perceived that they had maintained or improved CRF over the pandemic. Findings from this study suggest that a reduction in perceived CRF from pre-pandemic values in athletic patients in clinical practice may not result from population-wide pandemic changes in lifestyle. Worse health status and lower levels of moderate intensity PA were associated with perceived reduction in CRF over the pandemic in athlete patients.